Are We Overdiagnosing Pulmonary Embolism? Yes!: Paradigm Shift in Pulmonary Embolism. Issue 6 (November 2018) - Tan, Stephanie; Haramati, Linda B.
Abstract : Pulmonary embolism (PE) is a relatively common and potentially fatal pathology. Fear of missing the diagnosis is pervasive for physicians, including radiologists. However, as computed tomography pulmonary angiography technology and utilization have evolved over the years, we have gained an understanding that not all PEs are equal. As such, our interpretations of PE imaging studies must be enriched by this understanding and adapted to patient circumstances. Herein, we shine the light on overdiagnosis of PE, exploring the evidence, impact, costs, and consequences of overdiagnosis on the care of our patients.